Basal roughness of the East Antarctic Ice Sheet in relation to flow speed and basal thermal state. Issue 81 (April 2020) - Eisen, Olaf; Winter, Anna; Steinhage, Daniel; Kleiner, Thomas; Humbert, Angelika
Abstract: Basal motion of ice sheets depends in part on the roughness and material properties of the subglacial bed and the occurrence of water. To date, basal motion represents one of the largest uncertainties in ice-flow models. It is that component of the total flow velocity that can change most rapidly and can, therefore, facilitate rapid variations in dynamic behaviour. In this study, we investigate the subglacial properties of the East Antarctic Ice Sheet by statistically analysing the roughness of the bed topography, inferred from radio-echo sounding measurements. We analyse two sets of roughness parameters, one derived in the spatial and the other in the spectral domain, with two roughness parameters each. This enables us to compare the suitability of the four roughness parameters to classify the subglacial landscapes below the ice sheet. We further investigate the relationship of the roughness parameters with observed surface flow velocity and modelled basal temperatures of the ice sheet. We find that one of the roughness parameters, the Hurst exponent derived in the spatial domain, coincides with the thermal condition at the base of the ice sheet for slow flow velocities and varies with flow velocity.